IMPACT OF EMPLOYEE CYNICISM ON EMPLOYEE PERFORMANCE: THE MODERATING ROLE OF SUPERVISOR SUPPORT (Journal of Medical & Health Sciences Review, 2025)
Employee cynicism is a growing concern in workplace dynamics, particularly in healthcare organizations where teamwork is essential. This study examines the negative impact of employee cynicism on employee performance in public sector hospitals. Additionally, it explores the moderating role of supervisor support in mitigating these adverse effects. A quantitative approach was employed, using a structured questionnaire distributed among 250 nurses working in public sector hospitals in Rawalpindi, Pakistan. Data analysis was conducted using SPSS, applying regression and moderation analysis. Findings indicate that employee cynicism significantly reduces employee performance. However, supervisor support acts as a buffer, weakening this negative relationship. The study provides insights for healthcare administrators, emphasizing the need to foster supportive leadership to counteract workplace cynicism and enhance employee productivity.